Augmented Reality Animal Recognition Game: Enhancing Early Childhood Learning through Interactive Picture Guessing - Kukuh Harsanto; Anwar Rifai; This research focuses on developing an interactive learning game, (International Journal of Educatio Elementaria and Psychologia, 2024)
This research focuses on developing an interactive learning game, "Guess the Animal Picture," which utilizes augmented reality (AR) technology to help young children learn animal names in an engaging and effective manner. Traditional educational media, such as books or picture cards, often lack interactivity and fail to sustain children's attention over time. To address this issue, this study employs the 4D development method, which encompasses four stages: Define, Design, Develop, and Disseminate. In the Define stage, a needs analysis was conducted by examining early childhood education curricula, interviewing teachers, and observing challenges children face in learning animal names. The Design stage involved creating a game that integrates appealing visual elements, interactive sounds, and simple yet educational game mechanics, all enhanced by AR features that bring animals to life. During the Develop stage, a prototype was tested with a group of children to gather feedback, leading to further refinement of the game. Finally, in the Disseminate stage, the game was distributed to schools and early childhood education institutions, with training provided to teachers to optimize the game's use in educational settings. The results indicate that the "Guess the Animal Picture" game significantly improves children's ability to recognize and name animals while boosting their motivation to learn. Teachers and parents provided positive feedback, appreciating the game as an interactive and valuable learning tool. The study concludes that interactive, technology-based learning games, especially those incorporating AR, offer an effective solution for delivering a more engaging and efficient learning experience to young children